(untitled) (Eurasian Scientific Herald, 2022)
Scientifically studied global environmental problems with the participation of people, abiotic, biotic and anthropogenic factors, their causes, the pedagogical model of teaching students in higher education, the pedagogical foundations of protection from these problems. There is a scientific approach to the aspects that need to be considered when teaching students to ensure life safety.